Investigation of dynamic response changes in TLP type floating wind turbine with broken mooring lines - Mohammad Ali Nosratzadeh (نشریه مهندسی دریا, 2019)
As the cost of maintaining and repairing floating wind turbines is high compared with conventional turbines, one way to reduce these costs is to investigate the defects in these structures before any practical work. The importance of the stability and structural safety of wind turbines becomes more important with water depth growth and one of the most important factors for the stability of floating wind turbines is the system of mooring cables. In this paper, the effects of broken mooring cables on the dynamic response of a TLP type wind turbine is investigated. For this purpose, the floating wind turbine is modeled accurately with non-linear equations so that this modeling is responsive to large rotation angles that may be caused due to the cutting-off of the mooring cables. After concluding turbine modeling and applying forces, by cutting various mooring cables, the dynamic response changes of the structure are investigated. Studying the results shows that unlike other platforms, breaking of the mooring lines in a TLP-type turbine does not cause extreme oscillations and drifts in the structure.